Pastoral Edukatif Mengenai Seksual dalam Pembentukan Identitas Remaja Kristiani - Venly Mochtar; Jeane M. Tulung; Art Thomas; Heldy Rogahang (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this study is to describe and formulate theologically regarding the formation of adolescent identity in the congregation. This research uses qualitative research with literatur approach. The analysis and interpretation of the data show that: (1) the behavioral profile of adolescents in the formation of their identity is faced with various events, both social and personal interactions. Daily interactions and social media encourage teens to feel attracted to their friends and the opposite sex. The identity of the adolescent profile is also formed from the biological, psychological, and sociological aspects as well as the spiritual formation of adolescents. (2) The factors that influence promiscuity and free sex in their interactions are the lack of education about sex, sexuality, and communication between adolescents and their parents is not very open. Parents still consider it taboo when talking about sex and lack knowledge about the importance of sex education for children or adolescents. (3) The researcher emphasizes the role of the church to conduct an theological pastoral ethics ministry program regarding sex, sexuality, sexuality for adolescents and parents. Coaching for youth is carried out through Bible studies with the theme of sexuality. These educational service activities can equip youth in their lives.